(untitled) (Al-Mansour Journal, 2022)
The research aims to find out the nature of the talent management requirements and determine and diagnose the impact on the achievement of organizational commitment to human resources, and quality of services provided by the organization, the problem of research is expressed by many questions related with the nature of the interrelationships and effect among research’s variables. the descriptions - analytical approach, has been working in the Presidency to choose the University of Baghdad as a sample search of employees they are in units of individuals, faculty and identities, , And what constitutes a sample size of 60 individuals were provided with a questionnaire form for each of them specially prepared for this topic and then collected data was reached to group results using some statistical methods, The most prominent conclusions of the research importance of talents management and effects in organizational commitment and services quality , As for the most prominent recommendations one was the need to be aware of the fact that the University of Baghdad examined, talents management is one of the crucial elements in shaping and building organizational and enhance commitment and improve services quality produced from